Impact of the ST101 clone on fatality among patients with colistin-resistant Klebsiella pneumoniae infection. (3rd February 2018) - Can, Fusun; Menekse, Sirin; Ispir, Pelin; Atac, Nazlı; Albayrak, Ozgur; Demir, Tuana; Karaaslan, Doruk Can; Karahan, Salih Nafiz; Kapmaz, Mahir; Kurt Azap, Ozlem; Timurkaynak, Funda; Simsek Yavuz, Serap; et al.
Abstract: Objectives: We describe the molecular characteristics of colistin resistance and its impact on patient mortality. Methods: A prospective cohort study was performed in seven different Turkish hospitals. The genotype of each isolate was determined by MLST and repetitive extragenic palindromic PCR (rep-PCR). Alterations in mgrB were detected by sequencing. Upregulation of pmrCAB, phoQ and pmrK was quantified by RT–PCR. mcr-1 and the genes encoding OXA-48, NDM-1 and KPC were amplified by PCR. Results: A total of 115 patients diagnosed with colistin-resistant K. pneumoniae (ColR-Kp) infection were included. Patients were predominantly males (55%) with a median age of 63 (IQR 46–74) and the 30 day mortality rate was 61%. ST101 was the most common ST and accounted for 68 (59%) of the ColR-Kp. The 30 day mortality rate in patients with these isolates was 72%. In ST101, 94% (64/68) of the isolates had an altered mgrB gene, whereas the alteration occurred in 40% (19/47) of non-ST101 isolates. The OXA-48 and NDM-1 carbapenemases were found in 93 (81%) and 22 (19%) of the total 115 isolates, respectively. In multivariate analysis for the prediction of 30 day mortality, ST101 (OR 3.4, CI 1.46–8.15, P = 0.005) and ICU stay (OR 7.4, CI 2.23–29.61, P = 0.002) were found to be significantly associated covariates. Conclusions: Besides ICU stay, ST101 was found to be a significant independent predictor of patient mortality among those infected with ColR-Kp. A significant association was detected between ST101 and OXA-48. ST101 may become a global threat in the dissemination of colistin resistance and the increased morbidity and mortality of K. pneumoniae infection.